INOVASI LAYANAN WARGA DI BALAI RW SEBAGAI UPAYA PENINGKATAN KESADARAN ADMINISTRASI KEPENDUDUKAN OLEH PEMERINTAH KOTA SURABAYA - Lutfiah, Sunisfatul; Oktariyanda, Trenda Aktiva (Universitas Negeri Surabaya, 2024)
Public Services are activities or a series of activities that aim to meet community needs in accordance with statutory regulations. The government as a state servant as well as a public servant has the responsibility to carry out reforms and improve the quality of services so that they are in line with what is expected by the people who receive the services. One of the innovations launched by the Surabaya City Government is the Citizen Love Service innovation at the RW Hall. This research uses descriptive research methods with a qualitative approach. The focus of this research is indicators of Innovation Success Attributes according to Bugge et al., (2018). The subjects of this research were determined using a purposive sampling technique. The data collection techniques used were interviews, observation and documentation. Data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of this research show that the presence of Community Care Service Innovation as an effort to increase awareness of population administration can be seen that overall it has gone well but is not yet optimal. Dear Citizen Service as proof that the Surabaya City Government always supports the creation of innovation to improve services, it is proven that the Surabaya City Government received an award from the Ministry of Home Affairs (Kemendagri) in the 'Very Innovative City' category in 2023. Although there are several obstacles faced in the form of limited human resources and lack of supporting facilities such as bathrooms and prayer rooms. The suggestion put forward by the researchers is that it is necessary to carry out maximum socialization for each resident so that the innovation of the Dear Citizens service at the RW Hall can be known to the wider community.